Investigation and simulation of the transport of gas containing mercury in microporous silica membranes. (23rd November 2018) - Ji, Guozhao; George, Anthe; Skoulou, Vicky; Reed, Graham; Millan, Marcos; Hooman, Kamel; Bhatia, Suresh K.; Diniz da Costa, João C.
Graphical abstract: Highlights: Condensable Hg vapour effect on N2 permeation in microporous silica membrane. Significant Hg effect at 100 and 200 °C, though negligible at 300 °C. Hg effect correlated well with Hg adsorption on microporous silica xerogels. Oscillator model for gas transport including the Effective Medium Theory (EMT). The model's simulated results fitted well experimental results. Abstract: This work investigates the effect of condensable Hg vapour on the transport of N2 gas across cobalt oxide silica (CoOxSi) membranes. Experimental results suggest that Hg significantly affects N2 permeation at 100 and 200 °C, though this effect is negligible at 300 °C. This effect was found to have a correlation with Hg adsorption on CoOxSi xerogels. In order to understand the Hg effect in the transport phenomena of N2 permeation, the oscillator model was used to model gas transport through pores with different sizes. By including effective medium theory (EMT), the oscillator model fitted well the experimental results and gave good prediction of mass transfer in ultra-microporous materials with a tri-modal pore size distribution, such as silica membranes. It is postulated that Hg seeks lower level potentials in micro-pores, and therefore Hg molecules tend to block small pores (2.5–4 Å from 2.9 Å), or reduce the average pore size of larger pores (6.7–7.8 Å and 12–14 Å). Although N2 permeation decreased with the presence of Hg, it did not decrease when the Hg load was increased by a factor of ten; this strongly suggests the adsorption of Hg molecules in the smaller pores (2.5–4.0 Å), or along the pore wall for the larger pore ranges (6.7–7.8 Å and 12–14 Å).